Examining the role of Islamic Corporate Governance and climate change reporting in shaping stock prices of Mining Companies in the ISSI from 2020 to 2022 - Hasanah, Yaafiatul; Hastuti, Ely Windarti (Privietlab, 2025)
Mining companies sit at the crossroads of resource extraction and environmental fallout, and their decisions ripple across the planet's greenhouse-gas ledger. The current sustainability narrative places these firms in front and center, pressuring them to clean up operations before the next climate milestone arrives. This study probes whether Islam-inflected corporate governance principles codified by Sharia scholars in Indonesia make any discernible difference when firms' climate-related announcements hit the trading floor. The analysis zeroes in on stocks listed on the Indonesian Sharia Stock Index (ISSI) from 2020 to 2022, years when market nerves about carbon were unusually frayed. Data were collected from annual reports and sustainability disclosures by 28 mining players who habitually remained compliant, allowing for purposive sampling rather than random chance. EViews 12 then handled the panel-data regression, and the output was clear enough: richer climate disclosures buoyed prices, while the Islamic governance score sat on the sideline, glaring, but statistically mute. A final test tried pairing the two variables to see if the interaction sparked any life, yet the cross-term also landed with an insignificant p-value.